Metallocalixarene catalysts: α-olefin polymerization and ROP of cyclic esters. Issue 22 (20th May 2016) - Redshaw, Carl
Abstract : This perspective review discusses metallocalix[ n ]arene complexes that have been employed in either α-olefin polymerization or in the ring opening polymerization (ROP) of cyclic esters over the last 5 years. Abstract : This perspective review discusses metallocalix[ n ]arene complexes that have been employed in either α-olefin polymerization or in the ring opening polymerization (ROP) of cyclic esters over the last 5 years. Synthesis, molecular structure and catalytic potential are discussed. For α-olefin polymerization, systems based on early transition metals in combination with calix[ n ]arenes ( n = 4, 6 or 8), depleted calix[4]arenes or thia/sulfinyl/sulfonyl calix[4]arenes have been reported, and in some cases, are highly active. For the ROP studies, a number of the systems, typically of the early transition metals, only exhibit activity under robust conditions, whereas other systems, for example those of magnesium, demonstrate exceptional activity, immortal behaviour and intriguing stereoselectivity.